Development of onboard control system architecture for nanosatellites - Alipbayev, K.; Sarsenbayev, Y.; Mussina, А.; Nurgizat, Y. (Karagandy University of the name of acad. E.A. Buketov, 2022)
This article presents development of the architecture of the onboard control system. In particular, the hardware and circuit solutions in the development of the module are presented. Technical solutions, the concept of the mechanical layout of the onboard control system and block diagrams of the presented modules of the onboard complex are also discussed. Main functions of the on-board software are described in details, which will help in design and development of ultra-small artificial satellites. This article serves as a new approach for how to effectively configure and operate the on-board control system.
Keywords: onboard computer; cube sat; software defined radio; Field-Programmable Gate Array